Estimating Immigrant Earnings Profiles when Migrations are Temporary - Christian Dustmann; Joseph-Simon Görlach (Center for Economic Studies and ifo Institute (CESifo), 2016)
The assumption that all migrations are permanent, which pervaded the early microdata-based research on immigrant career profiles, is not supported by the empirical evidence. Rather, many – if not most – migrations appear to be temporary. In this paper, therefore, we illustrate the estimation challenges when migrations are temporary. As in an overwhelming share of the selective out-migration literature, our basic structure assumes that the process that determines out-migration is unrelated to other choices that affect wage growth, such as human capital investment or labour supply decisions, which greatly simplifies the analysis. When the choice of whether and when to out-migrate also affects decisions that determine wage growth, the problem becomes inherently dynamic and requires a more structural approach to estimation, which we briefly discuss.
Keywords: F22; J15; J31; J61; O15; 330; immigration; return migration; assimilation; earnings profile; selection